Kesesuaian Minat Karir dengan Keputusan Memilih Jurusan di Perguruan Tinggi - Abdiyatul Hasanah (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
Students compete to enroll in tertiary institutions with the majors they are interested in. Making a lot of students wrong in is a very important thing. Irene Guntur: